DEEP SPACE COMMUNICATION SYSTEMS AND TECHNOLOGY - Μπελάλη, Μαργαρίτα (Πανεπιστήμιο Πελοποννήσου, 2024)
This thesis explores the critical role of deep space communication systems and technologies in enabling successful space exploration and scientific discovery. In addition, this work contributes to the understanding of deep-space communication systems and technologies and offers guidance for future research and development. The study provides a comprehensive overview of the principles, challenges, and technologies associated with deep-space communication, as well as the design and operation of ground stations and antennas. Through an analysis of current communication protocols and standards, the thesis offers insights into how data is transmitted across vast distances in space. Case studies of successful deep space missions showcase the practical application of various communication strategies and technologies. The study concludes by examining emerging trends, challenges, and potential solutions for the future of deep space communication.
ΣΥΣΤΗΜΑΤΑ ΕΠΙΚΟΙΝΩΝΙΑΣ ΒΑΘΟΥ ΔΙΑΣΤΗΜΑΤΟΣ ΚΑΙ ΤΕΧΝΟΛΟΓΙΑ
Μ.Δ.Ε. 96